THE TRANSFORMATION OF CONVENTIONAL COOPERATIVES INTO SHARIA SAVING AND FINANCING COOPERATIVES (KSPPS): Study on KSPPS Tunas Artha Mandiri, Banjarsari-Ciamis - Sari Anggraeni; Helmi Maulana (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2022)
This study analyzes the reasons, supporting factors, process mechanisms, and effectiveness of conversion of Tunas Artha Mandiri Sharia Savings and Loans Cooperative (KSPPS) to convert. In addition, this study also aims to determine the conversion mechanism of Conventional Cooperatives into Savings and Loans Cooperatives and Sharia Financing at KSPPS Tunas Artha Mandiri, Banjarsari-Ciamis. The method is qualitative research, with data collection carried out through interviews. This study uses three types of informants: critical, primary, and additional. Data analysis followed the stages of data reduction, data presentation, and conclusion. The results showed (1) Two factors that encourage the Tunas Artha Mandiri Savings and Loans and Sharia Financing Cooperative (KSPPS) to convert, namely internal and external factors. Internal factors are driven by the performance of the Conventional Tunas Artha Mandiri Cooperative, which has sufficient capacity to transform. Meanwhile, external factors are due to policy encouragement from the head office, increased religiosity of human resources, and the lack of existing Sharia cooperatives. The conversion mechanism begins with the member approval meeting, preparation for conversion, changes to the articles of association, changes in business activities (transformation of institutions, systems, managers, members), ratification of the pieces of association, and until the application for a business license. Cooperative conversion is quite effective based on indicators of achievement of goals, integration, and adaptation.